2022
DOI: 10.1007/s11682-022-00735-5
|View full text |Cite
|
Sign up to set email alerts
|

Psychological resilience mediates the association of the middle frontal gyrus functional connectivity with sleep quality

Abstract: The ability to recover from stress, which is essential for sleep quality, is characterized as psychological resilience. Meanwhile, poor sleep quality is commonly related to low psychological resilience. However, the neurological underpinnings of psychological resilience, as well as the neural substrates of the links between psychological resilience and sleep quality in healthy brains, remain not well understood. Based on the recent studies that the middle frontal gyrus (MFG) acted a important role in psycholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 68 publications
1
4
0
Order By: Relevance
“…Moreover, age and gender were regarded as covariates. This approach is also in line with prior neuroimaging studies (Kong et al, 2020;Shi et al, 2022;Zhang et al, 2020). In this model, path a represented the effect of X on M, path b was calculated from regressing Y on M after controlling for X, path c' represented the direct effect of X on Y after controlling M, and path ab was equal to the multiplication of path a and path b, representing the indirect effect of X on Y through M. In addition, path c was equal to the sum of the direct effect and indirect effect, which is also recognized as the total effect.…”
Section: Mediation Analysissupporting
confidence: 70%
“…Moreover, age and gender were regarded as covariates. This approach is also in line with prior neuroimaging studies (Kong et al, 2020;Shi et al, 2022;Zhang et al, 2020). In this model, path a represented the effect of X on M, path b was calculated from regressing Y on M after controlling for X, path c' represented the direct effect of X on Y after controlling M, and path ab was equal to the multiplication of path a and path b, representing the indirect effect of X on Y through M. In addition, path c was equal to the sum of the direct effect and indirect effect, which is also recognized as the total effect.…”
Section: Mediation Analysissupporting
confidence: 70%
“…The possible reason for this is that psychological resilience contributes to positive emotional recovery [ 16 ]. Further, some other studies have found an association between sleep quality and psychological resilience [ 15 , 31 ]. The possible reason for this is that poor sleep quality leads to poor psychological stress capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Stress perception refers to the ability to perceive various negative external factors, which often serves as an important factor in predicting the occurrence of depression. The involvement of the MFG in emotional processing is related to psychological resilience ( 42 , 43 ). The MSFG and MFG are important components of the default network and frontal parietal network.…”
Section: Discussionmentioning
confidence: 99%